Pengaruh Kompetensi Guru Terhadap Kinerja Guru Pada SMKS PHT Cianjur - Hadi Sutrisno (STIKes Ibnu Sina Ajibarang, 2023)
Improving the quality of education is determined by the readiness of human resources involved in the education process. Teachers are one of the factors that determine the high quality of educational outcomes. Teachers are the most decisive component in the education system as a whole, which must receive central attention, because teachers are always related to any component in the education system. The same thing that is in SMKS PHT Cianjur with the targets and achievements of graduates that are matched with the industrial world, SMKS PHT Cianjur teachers must be equipped with appropriate skills. The results of the study found that competence has a positive effect on teacher performance.